Bringing my selves to work: a revisionist history of an academic career - Maitlis, S (SAGE Publications, 2024)
In this essay I share a decision I made early in my career, and repeatedly since then, to develop and segment different facets of myself, and I reflect on how my work and life might have differed had I made other choices. The preference to segment or integrate identities is a prominent part of the work-family literature (Dumas & Sanchez-Burks, 2015; Kossek et al., 2023), and while I also managed that boundary through much of my career, the boundary that I found more complicated was between two other identities: an organizational behavior (OB) professor, and a student and subsequently practitioner of counselling psychology and psychotherapy. At a glance, these may seem quite compatible activities, both social scientific endeavors fundamentally concerned with human behavior. Yet I experienced them as very different worlds and lived them quite separately. I also maintained a fairly impermeable boundary in my relationships with others in each world, speaking little about my academic experience and identity in the counselling psychology community, and even less about my psychotherapeutic interests in my academic life. Over time, and despite efforts to keep these worlds and identities apart, and even periodic thoughts of jettisoning one or the other, I found myself inadvertently integrating them – in my research, and to some extent in my emerging clinical practice. But I held back from fully owning or sharing my growing commitment to counselling psychology. In this revisionist reflection, I consider the consequences of this set of choices and what might have been different had I made others.